Pocahontas Incarcerated: An Activist’s Account of Early Twentieth-Century Native America - Szathmári, Judit (Hungarian Journal of English and American Studies, 2020)
Book review:Ackley, Kristina, and Cristina Stanciu, eds. Laura Cornelius Kellogg: Our Democracy and the American Indian and Other Works. New York: Syracuse UP, 2015. xxviii + 301 pages. ISBN 978-0-8156-3390-7. Hb. Npr.